Carl Nielsen and the Radio - Ketting, Knud (Carl Nielsen Studies, 2005)
On 1 April 1925 Denmark introduced national control of its hitherto privately run and relatively chaotic radio broadcasting. Denmark would quickly show itself to be one of Europe’s leading nations with regard to both the number of licence-paying listeners and the role of serious music in broadcasting policy. This situation was also reflected very directly in the case of Carl Nielsen. Out of the total of 5,802 performances of his work which the article’s author has been able to document until Nielsen’s death in 1931, 922 (or nearly a sixth) were either produced directly for radio (where in general all music was broadcast live), or broadcast via Danish and foreign radio. Nielsen’s attitude to the new medium was ambivalent from the beginning and gradually cooled. Indeed, the head of the Danish State Radio, kammersanger Emil Holm, was one of his friends, and Nielsen readily accepted when he was asked to conduct his own works at the concerts, which marked milestones in the newly founded Radio Orchestra’s development. He was also a member of the committee that decided in 1926 which type of transmitter the new radio station in Kalundborg would use. But he composed only a few, not especially important new works for radio use, and does not seem to have been clear about what the radio medium meant for his music at a European level. The article presents a series of hitherto unknown documents concerning Carl Nielsen’s relationship to the radio medium, and includes a schematic chart in the appendix offering a detailed overview of which Nielsen works a listener could have heard, and when, on Danish and foreign radio stations up until the composer’s death.